Analysis of a Tall Structure Considering Diaphragm Irregularity Using Analysis Tool - Khan, Ankit Bhadra; Khan, Anita Chaturvedi; Khan, Lokesh Singh (International Journal of Scientific Research in Civil Engineering, 2024)
Many buildings in the present scenario have irregular configurations both in elevation and plan. This in future may be subject to devastating earthquakes. It is necessary to identify the performance of the structures to withstand disaster for both new and existing buildings. Now a days openings in the floors is common for many reasons like stair cases, lighting architectural etc., these openings in diaphragms cause stresses at discontinues joints with building elements. Discontinuous diaphragms are designed without stress calculations and are thought-about to be adequate ignoring any gap effects. Earthquakes are natural dangers under which catastrophes are primarily caused by destruction or fall of structures.